Encyclopedia of Tourism - Jafari, Jafar; Xiao, Honggen (Springer International Publishing : Imprint: Springer, 2016)
This encyclopedia is the most comprehensive and updated source of reference in tourism research and practice. It covers both traditional and emerging concepts and terms and is fully international in its scope. More than 700 contributions of 766 internationally renowned experts from 113 countries provide a definitive access to the knowledge in the field of tourism, hospitality, recreation and related fields. All actors in this field will find reliable and up to date definitions and explanations of the key terms of tourism in this reference work. Tourism is the largest industry worldwide and is the main source of income for many countries. With both, this practical impact of tourism and a rapidly developing academic field, with a growing number of university courses and degrees in tourism, and a flourishing research, this encyclopedia is the epicenter of this emerging and developing discipline. .